Design and Construction with Curved Glass. Issue 5 (22nd October 2018) - Fildhuth, Thiemo; Schieber, Roman; Oppe, Matthias
ABSTRACT: Curved glass is increasingly used in modern architecture, driven by free‐form design, the desire for smooth, continuously curved facades and new or improved manufacturing methods. Permanent curvature is obtained by thermal bending, whereas elastic cold bending results in a reversible curved glass shape stabilized either by fixing upon a substructure or by lamination with shear‐stiff interlayers. However, for the application in building projects many mutually depending factors such as the achievable geometrical shape and curvature, glass dimensions, potential residual stress, load bearing behavior, applicability for IGUs, coating options, cost, necessary supports, lamination, interlayer type or the optical quality have to be respected. The present paper contributes to creating a design basis regarding the use of curved architectural glass by comparing the typical properties, assets and limitations of the above‐mentioned types and by illustrating their application through project examples.